2012
DOI: 10.1186/1471-2148-12-125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of a-kinase anchoring protein (AKAP)-7: implications in comparative PKA compartmentalization

Abstract: BackgroundA-Kinase Anchoring Proteins (AKAPs) are molecular scaffolding proteins mediating the assembly of multi-protein complexes containing cAMP-dependent protein kinase A (PKA), directing the kinase in discrete subcellular locations. Splice variants from the AKAP7 gene (AKAP15/18) are vital components of neuronal and cardiac phosphatase complexes, ion channels, cardiac Ca2+ handling and renal water transport.ResultsShown in evolutionary analyses, the formation of the AKAP7-RI/RII binding domain (required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…There is a clear contrast between this novel interaction described for P-Rex1 and PKA and the classical mechanism of interaction of PKA with AKAPs, which regularly occurs through the N terminus of types I and II regulatory subunits (51). Detailed biochemical, cellular, and structural studies have revealed a plethora of AKAPs that interact with the N terminus of PKA regulatory subunits and provide a mechanistic basis by which type II holoenzymes, in particular, are localized to different subcellular compartments (52)(53)(54)(55). Less information is available for type I PKA, although some AKAPs are dual specific and bind to both RI and RII subunits, whereas a few such as sphingosine kinase-interacting protein (SKIP) and the recently discovered small myristoylated and palmitoylated AKAP are RI-specific (56 -58).…”
Section: P-rex1 Dh-ph Catalytic Module Is Also Inhibited By the C-termentioning
confidence: 99%
“…There is a clear contrast between this novel interaction described for P-Rex1 and PKA and the classical mechanism of interaction of PKA with AKAPs, which regularly occurs through the N terminus of types I and II regulatory subunits (51). Detailed biochemical, cellular, and structural studies have revealed a plethora of AKAPs that interact with the N terminus of PKA regulatory subunits and provide a mechanistic basis by which type II holoenzymes, in particular, are localized to different subcellular compartments (52)(53)(54)(55). Less information is available for type I PKA, although some AKAPs are dual specific and bind to both RI and RII subunits, whereas a few such as sphingosine kinase-interacting protein (SKIP) and the recently discovered small myristoylated and palmitoylated AKAP are RI-specific (56 -58).…”
Section: P-rex1 Dh-ph Catalytic Module Is Also Inhibited By the C-termentioning
confidence: 99%
“…Manner. Long isoforms of AKAP18 encode targeting sequences that direct the anchoring protein to a variety of other subcellular locations (37,44). For example, AKAP18γ and -δ are sequestered at the sarcoplasmic reticulum through protein-protein interactions with SERCA2 calcium reuptake channels, whereas in kidney collecting ducts, AKAP18δ is a component of intracellular vesicles (38,39).…”
Section: Akap18 Long Isoforms Transit To the Nucleus In A Pka-dependentmentioning
confidence: 99%
“…1B) or AKAP18d (encoded by AKAP7 gene [25]) (data not shown). Above-mentioned AKAPs were tested first because its presence in liver was previously reported [26][27][28].…”
Section: The Activation Of Adenosine Receptors Involves Specific Acs mentioning
confidence: 99%
“…1A), and by treatment with antibodies against AKAP79/150 (encoded by AKAP5 gene according to the Human Genome Organization (HUGO) gene nomenclature committee [25]), but not D-AKAP2 (encoded by AKAP10 gene [25]) (Fig. Above-mentioned AKAPs were tested first because its presence in liver was previously reported [26][27][28]. Above-mentioned AKAPs were tested first because its presence in liver was previously reported [26][27][28].…”
Section: Introductionmentioning
confidence: 99%